Perlindungan Hukum Non Yudisial terhadap Perbuatan Hukum Publik oleh Pemerintah - Hari Sugiharto; Bagus Oktafian Abrianto (Yuridika, 2018)
The enactment of Law Number 30 of 2014 on Government Administration had given the changes to the authority of the State Administrative Court. There are two mechanism of the case investigation in the State Administrative Court in providing legal protection against a lawsuit or petition filed by the public. The first mechanism is to file a lawsuit directly to the State Administrative Court. The second mechanism is to resolve internal disputes within the government before filing a lawsuit to the Administrative Courts. There are two mechanisms of the case investigation prove that the existence of discrimination for people who seek justice in the case investigation system in the State Administrative Court. This research focus on an issues first the nature of public legal action by the government in government administration and second Ratio legis non-judicial legal protection against public legal acts  by the government. The results which have to be achieved are to provide the prescription of essential truth. There are several problems approach used in this study, such as statute approach, conceptual approach, and case approach.